Large-size quartz glass and preparation method and system thereof
By dehydroxylation and sintering the silica loose body, and differential heat treatment and pressure forming are carried out in the mold cavity, the problem of poor optical uniformity of large-size quartz glass in the prior art is solved, and efficient preparation of large-size Quartz glass with low hydroxyl content meets the needs of high-tech fields.
Patent Information
- Application Number
- CN202210972740.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-15
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-08-15
AI Technical Summary
It is difficult to prepare quartz glass with large size, low hydroxyl content and good optical uniformity in the prior art, especially quartz glass with a diameter of more than 100mm, which has metal impurities and bubble problems and cannot meet the needs of the high-tech field.
By dehydroxylation and sintering the silica loose body, a quartz glass blank is obtained and differential heat treatment and pressure application are carried out in the mold cavity. The partition temperature and pressure application forming technology of the mold cavity are used to avoid the extrusion process The generation of mid-stripes and bubbles improves optical uniformity.
The preparation of large-size quartz glass with a diameter of up to 300mm to 400mm and a thickness of up to 300mm to 400mm is achieved. The metal impurity content and hydroxyl content are less than 1ppm, and the optical uniformity is less than 12×10-6, meeting the needs of high-tech fields. .
Smart Images

Figure CN115259655B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of optical quartz glass manufacturing, and in particular relates to large-size quartz glass and a preparation method and system thereof. Background Art
[0002] Quartz glass is a glass composed of a single component of silicon dioxide. Quartz glass is widely used in high-tech fields such as aerospace, semiconductors, and nuclear technology. With the rapid development of aerospace, semiconductors, and nuclear technology, all walks of life have higher and higher requirements for the performance and quality of quartz glass. The preparation process of quartz glass is an important factor affecting the performance and quality of quartz glass.
[0003] There are two methods for preparing quartz glass: direct method and indirect method. The direct method mainly uses natural quartz or silicon-containing compounds as raw materials, and uses high-temperature melting method, electric melting method, chemical vapor deposition method (CVD), and ion chemical vapor deposition method (POD) to produce quartz glass. Due to its own process limitations, the quality of the produced quartz glass is poor, the content of metal impurities and hydroxyl groups is high, and there are many bubbles in the glass, which seriously affects its optical properties and cannot meet the needs of the optoelectronic technology field.
[0004] The indirect method mainly uses silicon-containing compounds as raw materials, and uses vapor deposition (VAD) to prepare silica powder, and then removes hydroxylation and purification of the silica powder, and finally sintering the silica powder into quartz glass at high temperature. By removing hydroxylation and purification of the powder intermediate, the metal impurity content and hydroxyl content in the quartz glass can be controlled at a low level, but due to the size of the powder intermediate, the diameter of the quartz glass obtained by the indirect method is usually 100mm to 200mm, and it is difficult to prepare quartz glass of larger size.
[0005] Therefore, how to achieve the preparation of high-quality quartz glass with large size, low hydroxyl content and good optical uniformity is a technical problem to be solved urgently in this field. Summary of the invention
[0006] The invention provides a large-size quartz glass and a preparation method and system thereof, which can produce large-size, low-hydroxyl and good optical uniformity quartz glass.
[0007] In one aspect of the present invention, a method for preparing quartz glass is provided, comprising the following steps: performing a dehydroxylation treatment and a sintering treatment on a silicon dioxide loose body to obtain a quartz glass blank; placing the quartz glass blank in a mold cavity for a first differential heat treatment and applying pressure to the quartz glass blank in a first direction to obtain quartz glass; the mold cavity sequentially includes a first temperature region and a second temperature region along the first direction, and the quartz glass blank includes a second portion corresponding to the second temperature region and a first portion corresponding to at least a portion of the first temperature region; in the first differential heat treatment, the temperature of the second temperature region is higher than the temperature of the first temperature region, and the temperature of the second temperature region is not less than 1600° C.; in the pressure treatment, the deformation speed of the quartz glass blank is not higher than 10 mm / min; the mold cavity has a bottom wall for receiving the quartz glass, and the bottom wall has a depression.
[0008] According to one embodiment of the present invention, before the first differential heat treatment, the quartz glass blank is further subjected to a first soaking treatment; in the first soaking treatment, the temperature T1 of the first temperature zone is equal to the temperature T2 of the second temperature zone, 1300°C≤T1, T2<1600°C, and the time is not less than 60 minutes.
[0009] According to one embodiment of the present invention, in the first differential heat treatment, the temperature of the first temperature zone is T1, and the temperature of the second temperature zone is T2, wherein 1300°C≤T1<1600°C, and 1600°C≤T2≤1800°C.
[0010] According to one embodiment of the present invention, after the pressure treatment, a second uniform heat treatment is also included; the temperature of the second uniform heat treatment is 20°C to 50°C higher than the temperature of the second temperature zone in the first differential heat treatment, and the time is not less than 10 minutes.
[0011] According to one embodiment of the present invention, the heating rate of each heat treatment is 3° C. / min to 8° C. / min.
[0012] According to one embodiment of the present invention, during the pressurizing process, the deformation speed of the quartz glass blank is 3 mm / min to 10 mm / min.
[0013] According to one embodiment of the present invention, the mold cavity has a bottom wall for receiving quartz glass, the bottom wall includes a recessed portion located in the center and a planar portion arranged around the recessed portion, and the recessed portion is recessed in a direction away from the center of the mold cavity.
[0014] A second aspect of the present invention provides quartz glass produced by the above-mentioned preparation method.
[0015] According to a third aspect of the present invention, a quartz glass preparation system is provided for implementing the above-mentioned preparation method, the system at least comprising: a sintering furnace for performing dehydroxylation and sintering treatments on a silicon dioxide loose body; a trough sinking furnace comprising a furnace shell, a mold having a mold cavity, a pressure unit, a first heating unit and a second heating unit; the mold cavity is located in a heating cavity formed by the furnace shell, the first heating unit and the second heating unit are located between the furnace shell and the mold and are arranged in sequence along a first direction; the pressure unit is arranged in the mold cavity and reciprocates in the mold cavity along the first direction.
[0016] According to one embodiment of the present invention, the mold cavity has a bottom wall for receiving quartz glass, the bottom wall includes a recessed portion located in the center and a planar portion arranged around the recessed portion, and the recessed portion is recessed in a direction away from the center of the mold cavity.
[0017] The implementation of the present invention has at least the following beneficial effects:
[0018] The present invention can fully remove the metal impurities and hydroxyl groups remaining in the silica soot body by performing a dehydroxylation treatment on the silica soot body, and then perform a sintering treatment to make the silica soot body preliminarily vitrified to obtain a quartz glass blank; the present invention places the quartz glass blank in a mold cavity, and applies pressure to the quartz glass blank along a first direction to obtain a large-sized quartz glass having the same shape as the mold cavity; at the same time, by performing a first differential heat treatment on the quartz glass blank, the quartz glass blank is gradually softened and formed, and the generation of stripes and bubbles during the extrusion process is avoided, and the optical uniformity of the quartz glass can be effectively improved.
[0019] The quartz glass prepared by the preparation method of the present invention can achieve an optical uniformity of 12×10 -6 The metal impurity content can reach below 1ppm, the hydroxyl content can reach below 1ppm, the quartz glass diameter can reach 300mm~400mm, and the thickness can reach 300~400mm. It has the advantages of large size, low hydroxyl content, and good optical uniformity. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic diagram of the structural cross section of a tank sinking furnace in one embodiment of the present invention;
[0021] Figure 2 is a schematic structural diagram of a deposition device in one embodiment of the present invention;
[0022] Description of reference numerals:
[0023] 1-furnace shell; 2-cylinder; 3-pressing plate; 3a-pressing plate mold; 4-quartz glass blank; 5-mold; 5a-bottom wall; 51a-recessed portion; 52a-flat portion; 6a-first heating unit; 6b-second heating unit; 7-insulating plate; 8-mold cavity; 101-quartz tail handle; 102-metal suspension rod; 103-silicon dioxide loose body; 11-furnace shell; 11a-deposition cavity; 12-extension shell; 12a-extension cavity; 14-deposition torch; 15-PLC system; 16-infrared thermal imager; 17-exhaust system. DETAILED DESCRIPTION
[0024] The specific implementations listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementations obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] The present invention provides a preparation method of large-size quartz glass, comprising the following steps: performing dehydroxylation treatment and sintering treatment on a silicon dioxide loose body to obtain a quartz glass blank; placing the quartz glass blank in a mold cavity to perform a first differential heat treatment and applying pressure to the quartz glass blank in a first direction to obtain quartz glass; wherein the mold cavity includes a first temperature region and a second temperature region in sequence along the first direction, and the quartz glass blank includes a second portion corresponding to the second temperature region and a first portion corresponding to at least a portion of the first temperature region; in the first differential heat treatment, the temperature of the second temperature region is higher than the temperature of the first temperature region, and the temperature of the second temperature region is not less than 1600°C.
[0026] The present invention does not limit the first direction. For example, the first direction may be the height extension direction of the mold cavity. The mold cavity is divided into a first temperature zone and a second temperature zone along the first direction, wherein the second temperature zone is closer to the first direction than the first temperature zone.
[0027] When the quartz glass blank is placed in the mold cavity, the height of the mold cavity can be greater than or equal to the height of the blank, ensuring that the blank has a portion corresponding to the mold cavity. Along the first direction, the blank includes a second portion corresponding to the second temperature zone, and a first portion corresponding to at least a portion of the first temperature zone. At this time, the second temperature zone can perform heat treatment on the second portion, and the first temperature zone can perform heat treatment on the first portion.
[0028] It should be noted that the first part and the second part of the quartz glass blank of the present invention refer to the blank before the press treatment.
[0029] Specifically, the method of the present invention uses silicon dioxide loose body as the initial raw material for dehydroxylation treatment and sintering treatment to obtain a quartz glass blank. The present invention also places the quartz glass blank in a mold cavity for a first differential heat treatment and a pressure treatment to finally obtain quartz glass.
[0030] The present invention uses silicon dioxide soot body as raw material, removes hydroxyl groups and metal impurities in the soot body through dehydroxylation treatment, and after the dehydroxylation treatment is completed, further performs sintering treatment to vitrify the silicon dioxide soot body to form a quartz glass blank.
[0031] The first differential heat treatment refers to placing the quartz glass blank in the mold cavity, and heating the blank in different areas by making the temperature of the second temperature area of the mold cavity higher than the temperature of the first temperature area. Since the temperature of the second temperature area is not less than 1600°C in the first differential heat treatment, the second part of the blank softens first, and the temperature of the first temperature area of the mold cavity is relatively lower, so that the first part of the blank corresponding to the first temperature area can maintain a relatively stable state.
[0032] At the same time, the blank is pressurized along the first direction so that the first softened part of the blank is formed under the action of pressure. During the pressurization process, the height of the blank gradually decreases along the first direction, and the remaining blank gradually moves to the second temperature area of the mold cavity. Under relatively higher temperature conditions, it is also gradually softened. Through pressure molding, in the above-mentioned gradual softening and molding process, the generation of stripes and bubbles during the extrusion process can be avoided.
[0033] It can be seen that the present invention first performs dehydroxylation and sintering treatment on the silicon dioxide loose body to obtain a quartz glass blank with low hydroxyl content and metal content, and then places the quartz glass blank in a mold cavity, performs a first differential heat treatment on the quartz glass blank, and applies pressure to the quartz glass blank along a first direction, which can ensure that the quartz glass blank is gradually softened and formed, avoid the generation of stripes and bubbles during the extrusion process, and effectively improve the optical uniformity of the quartz glass. In addition, large-sized quartz glass consistent with the shape of the mold cavity can also be obtained.
[0034] The silicon dioxide loose body of the present invention is formed by the aggregation of nano silicon dioxide particles. The present invention does not limit the preparation method of the silicon dioxide loose body. In a possible embodiment, the silicon dioxide loose body is prepared by chemical vapor deposition using a silicon-containing compound as a raw material. The silicon dioxide loose body is usually cylindrical, for example, it can be a cylindrical body with a bottom diameter of 240 mm to 400 mm and a height of 1.2 m to 2 m.
[0035] The dehydroxylation treatment is usually carried out by conventional methods in the art. For example, a dehydroxylation gas containing halogen elements can be used to carry out the dehydroxylation treatment on the silica soot body, which can effectively reduce the hydroxyl content and metal impurity content in the later quartz glass blank. On the premise of continuing the advantages of the silica soot body prepared by chemical vapor deposition, the negative impact of impurities such as hydroxyl groups and metals on the optical properties of the quartz glass can be effectively reduced, and the optical uniformity of the quartz glass can be improved.
[0036] The dehydroxylation gas containing halogen elements includes gases containing halogen elements, such as fluorine gas, chlorine gas, bromine steam, sulfur dioxide, etc. An inert gas can be used as a protective gas for the dehydroxylation gas, such as helium.
[0037] In the present invention, conventional methods can be used for sintering treatment, for example, the following steps may be included: heating the dehydroxylated silica soot body to a sintering temperature, sintering the silica soot body, and after the sintering treatment, cooling the body to obtain a quartz glass blank.
[0038] During the sintering process, the heating process can maintain a certain heating rate, so that the silica soot body is fully and evenly heated and slowly completes the vitrification process, thereby ensuring that the obtained quartz glass has good optical uniformity. After the silica soot body is sintered, the temperature is reduced at a certain cooling rate. Slow cooling helps to improve the internal stress defects of the quartz glass and produce low-stress quartz glass. The combination of slow high-temperature sintering and slow cooling can effectively reduce the internal stress of the quartz glass, thereby improving the uniformity of the quartz glass.
[0039] The above-mentioned dehydroxylation and sintering treatment can be completed in one sintering furnace, avoiding possible pollution during material transfer, reducing the impurity content in the quartz glass, and improving the uniformity of the quartz glass. In addition, during the dehydroxylation and sintering treatment of the silica loose body, the temperature can be continuously increased or kept constant, reducing the waste of resources caused by repeated heating and cooling, reducing production costs, and the preparation process is green and environmentally friendly.
[0040] Usually the conditions for dehydroxylation treatment are: temperature of 1210℃~1290℃, and time of not less than 10h; the temperature of sintering treatment is higher than that of dehydroxylation treatment, and usually the conditions for sintering treatment are: temperature of 1450℃~1600℃, and time of sintering treatment is not less than 10h.
[0041] In the present invention, before placing the quartz glass blank in the mold cavity for the first differential heat treatment, the process further includes subjecting the quartz glass blank to a uniform heat treatment.
[0042] During the heat treatment, the temperature T1 of the first temperature zone is equal to the temperature T2 of the second temperature zone, 1300℃≤T1, T2<1600℃, so that the blank is in a critical state of melting, and the temperature is maintained for not less than 60 minutes. It is fully heated to ensure that the temperature inside and outside the blank remains consistent.
[0043] In the present invention, in the first differential heat treatment, the temperature of the first temperature zone is T1, wherein T1 satisfies 1300° C. ≤ T1 < 1600° C., and the temperature of the second temperature zone is T2, wherein T2 satisfies 1600° C. ≤ T2 ≤ 1800° C. Usually, the above heat treatment temperature is maintained for at least 10 minutes, and after the second part of the blank is completely melted, the quartz glass blank is subjected to pressure treatment to be formed.
[0044] In the specific implementation process of the present invention, the quartz glass blank is placed in a vertical mold cavity, such as Figure 1 As shown, the height direction of the quartz glass blank is consistent with the height direction of the mold cavity, and the first direction can be the direction from A to B, so that the direction where the height of the blank is located is parallel to the first direction. The mold cavity includes a first part and a second part in sequence along the direction from A to B.
[0045] In the above specific implementation process, the blank is subjected to pressure treatment along the direction from A to B. During the pressure treatment, the deformation speed of the quartz glass blank is 3 mm / min to 10 mm / min, that is, the quartz glass blank is subjected to pressure treatment along the direction from A to B, so that the height of the quartz glass blank decreases at a rate of 3 mm / min to 10 mm / min. Figure 1 As shown, the mold cavity 8 may be cylindrical, and by applying an external force to the quartz glass blank 4 along a first direction, a large-sized quartz glass having the same shape as the mold cavity can be obtained.
[0046] The mold cavity 8 has a bottom wall 5a for receiving the quartz glass. The bottom wall 5a includes a concave portion 51a located at the center and a flat portion 52a arranged around the concave portion 51a. The concave portion 51a is concave in a direction away from the center of the mold cavity 8.
[0047] Specifically, the recessed portion 51a may be in an arc shape or in a step shape, preferably in an arc shape, which is conducive to the molding of quartz glass.
[0048] The quartz glass blank 4 is fixed in the mold cavity 8, specifically, the first direction can be directed to the concave portion 51a. At the same time, the bottom surface of the quartz glass blank 4 is arranged opposite to the concave portion 51a, so as to ensure that during the pressurization process, the blank 4 is first formed in the concave portion 51a, and then gradually formed and extended to the flat portion 52a based on this, to reach the target outer diameter. By first forming the blank in the concave portion and then gradually extending the blank to the flat portion for forming, this process can avoid the generation of stripes and bubbles caused by irregular extrusion, which affects the uniformity of the quartz glass.
[0049] In the present invention, the pressure treatment may be extrusion molding of the quartz glass blank according to a constant extrusion tension, or may be segmented extrusion molding of the quartz glass blank.
[0050] In the specific implementation process of the present invention, the height drop rate of the quartz glass blank 4 can be set to 3mm / min to 5mm / min, and after the blank 4 completely fills the recessed portion 51a, the constant pressure is adjusted to apply pressure, so that the height drop rate of the quartz glass blank 4 is maintained at 5mm / min to 10mm / min. The extrusion tension can be -5N to -2N, where the negative sign indicates the direction, and the tension is negative during extrusion.
[0051] After the pressure treatment, the second differential heat treatment is also performed on the blank after pressure forming, and the temperature of the second differential heat treatment is 20°C to 50°C higher than the temperature of the second temperature zone in the first differential heat treatment, and the time is not less than 10 minutes. The blank after forming is kept under the pressure of the pressure and the temperature of the second differential heat treatment, which can effectively remove the tiny bubbles remaining in the blank, which is beneficial to the optical uniformity of the quartz glass.
[0052] Usually, the height of the blank after press forming is not higher than the height of the second temperature zone. Therefore, in the specific implementation of the present invention, in the second differential heat treatment, the temperature of the first temperature zone may not be equal to the temperature of the second temperature zone. It is sufficient to increase the temperature of the second temperature zone in the second differential heat treatment by 20°C to 50°C on the basis of the first differential heat treatment. The temperature of the first temperature zone may remain unchanged on the basis of the first differential heat treatment.
[0053] In the present invention, the heating rate of each heat treatment is 3°C / min to 8°C / min. The temperatures of the uniform heat treatment, the first differential heat treatment, and the second differential heat treatment can be achieved by slowly heating, and the heating rate of each heat treatment is independently selected from 3°C / min to 8°C / min. Slow heating can make the blank heated uniformly, which helps to improve the uniformity of the quartz glass.
[0054] In the present invention, after dehydroxylation and sintering, the obtained blank is subjected to differential heat treatment, pressing and other treatments, which can not only shape the blank, but also reshape the internal structure of the blank, which is beneficial to improving the optical uniformity of the quartz glass.
[0055] The present invention also provides a quartz glass, which is prepared by the above-mentioned preparation method and has the characteristics of large size, high uniformity, and low hydroxyl group, and the optical uniformity can reach 12×10 -6 Below, further up to 8×10 -6 Below, further can reach 5×10 -6 Below; the metal impurity content can reach below 1ppm, the hydroxyl content can reach below 1ppm, the diameter of the quartz glass can reach 300mm~400mm, and the thickness can reach 300mm~400mm.
[0056] In the present invention, the silicon dioxide loose body is prepared by chemical vapor deposition. The chemical vapor deposition process can be carried out in a deposition device, such as Figure 2 As shown, the deposition equipment includes a furnace shell 11, a deposition chamber 11a formed by the furnace shell 11, an extension shell 12, an extension chamber 12a formed by the extension shell 12, a deposition torch 14, an infrared thermal imager 16, a PLC control system 15 and an exhaust system 17.
[0057] The deposition chamber 11a is connected to the extension chamber 12a, and the diameter of the extension chamber 12a is smaller than that of the deposition chamber 11a. A metal suspension rod 102 is provided above the extension chamber 12a, and a quartz tail handle 101 is installed on the metal suspension rod 102. When the silicon dioxide loose body is continuously deposited in the chamber, the upper suspension rod moves slowly upward during the deposition process, and the deposited silicon dioxide loose body is gradually moved to the extension chamber.
[0058] The deposition torch 14 is arranged on the furnace shell 11 and is used to introduce hydrogen, oxygen and silicon-containing compound raw materials into the deposition chamber 11a. During the deposition process, the silicon-containing compound raw materials enter from the bottom of the deposition torch 14, react in the torch, and then silicon dioxide powder is sprayed out from the upper torch port. The silicon dioxide powder gradually adheres to the quartz tail handle 101 in the chamber, wherein the quartz tail handle 101 is rotated at a certain speed by the metal suspension rod 102, and gradually deposits to form a silicon dioxide loose body 103.
[0059] During the deposition process, the infrared thermal imager 16 can perform real-time analysis and monitoring of the heat distribution in the deposition chamber 11 a and feed it back to the PLC system 15 .
[0060] The exhaust system 17 is arranged in the furnace shell 11, and can automatically control the exhaust in the deposition chamber 11a according to the feedback signal of the infrared thermal imager 16. The exhaust system 17 is composed of a series of automatic exhaust devices and exhaust ports of different shapes.
[0061] A programmable logic controller (PLC) system 15 can automatically collect information and perform control according to a programmed program, wherein the infrared thermal imager 16, the exhaust system 17 and the deposition torch 14 are connected to the PLC system 15 via signal lines.
[0062] On the one hand, the above-mentioned PLC system 15 can control the heat increasing end in the deposition chamber 11a by adjusting the flow rate of the deposition torch 14, and on the other hand, it can control the heat reducing end of the deposition chamber 11a by adjusting the exhaust position, exhaust speed, exhaust volume and other parameters of the exhaust system 17, so that the heat in the deposition chamber 11a can be evenly distributed, and the airflow in the deposition chamber 11a can flow stably, and a stable dynamic balance system can be formed in the deposition chamber 11a, which is conducive to the deposition of a highly uniform silica loose body 13.
[0063] The present invention also provides a quartz glass preparation system for implementing the above-mentioned preparation method, the system at least comprising: a sintering furnace for dehydroxylation and sintering of silicon dioxide loose body; Figure 1 As shown, the trough sinking furnace includes a furnace shell 1, a mold 5 having a mold cavity 8, a pressure unit, a first heating unit 6a and a second heating unit 6b; the mold cavity 8 is located in the heating cavity formed by the furnace shell 1, the first heating unit 6a and the second heating unit 6b are located between the furnace shell 1 and the mold 5 and are arranged in sequence along a first direction; the pressure unit is arranged in the mold cavity and reciprocates in the mold cavity 8 along the first direction.
[0064] The sintering furnace can be a conventional device in the art, such as a vertical sintering furnace. The vertical sintering furnace comprises a furnace body, a graphite furnace core tube, a quartz furnace core tube, a heating unit, an air inlet and an air outlet.
[0065] The graphite furnace core tube wraps the quartz furnace core tube, the furnace body wraps the graphite furnace core tube, and the heating unit is arranged between the furnace body and the graphite furnace core tube. Placing the silicon dioxide loose body in the quartz furnace core tube can ensure that the silicon dioxide loose body is not contaminated by metal impurities.
[0066] The air inlet and the air outlet are connected with the quartz furnace core tube. The air inlet can be used to introduce dehydroxylation gas and protective gas, and the air outlet is used to discharge waste gas.
[0067] In the tank sink furnace, the first heating unit 6a and the second heating unit 6b are arranged in sequence along the first direction, and the temperature can be controlled independently. The first heating unit 6a and the second heating unit 6b correspond to the first temperature zone and the second temperature zone of the mold cavity respectively. Specifically, the first heating unit 6a can be used to control the temperature of the first temperature zone, and the second heating unit 6b can be used to control the temperature of the second temperature zone.
[0068] The first heating unit 6a and the second heating unit 6b can be graphite heating bodies made of graphite material. A heat insulation board 7 can also be arranged between the first heating unit 6a, the second heating unit 6b and the furnace shell 1, which can be, for example, a graphite heat insulation material.
[0069] like Figure 1 As shown, the first direction is from A to B.
[0070] The pressure unit may include a cylinder 2 and a pressing plate 3, wherein the cylinder 2 can control the pressing plate 3 to reciprocate in the first direction in the mold cavity 8. A sensor is also provided on the cylinder 2, which can automatically control the descending speed of the cylinder according to the set extrusion tension, so that during the entire pressure process, the quartz glass blank 4 can be deformed at a uniform and slow speed until extrusion molding, and the descending speed of the cylinder is usually equal to the deformation speed of the quartz glass blank 4. A pressing plate mold 3a is provided on one side of the pressing plate 3 close to the mold cavity, which is used to fix the quartz glass blank 4 in the mold cavity.
[0071] The mold 5 with the mold cavity 8 is mainly composed of a U-shaped graphite mold and a bottom wall 5a for receiving the quartz glass. The bottom wall 5a includes a recessed portion 51a located in the center and a flat portion 52a arranged around the recessed portion 51a. The recessed portion 51a is recessed in a direction away from the center of the mold cavity 8. The bottom surface of the blank 4 is arranged opposite to the recessed portion 51a, and the quartz glass blank 4 can be fixed in the mold cavity 8 by cooperating with the pressing plate mold 3a on the pressing plate 3 through the bottom wall 5a. The bottom wall 5a can be a graphite bottom plate.
[0072] In the present invention, the above-mentioned quartz glass preparation system is used to implement the quartz glass preparation method, and the specific process steps are as follows:
[0073] Step 1, placing the silicon dioxide loose body in a sintering furnace, first introducing an inert gas into the sintering furnace, heating the sintering furnace to a dehydroxylation temperature, and preheating; then introducing a dehydroxylation gas containing a halogen element into the sintering furnace to perform a dehydroxylation treatment; after the dehydroxylation treatment is completed, first stop introducing the dehydroxylation gas containing a halogen element into the sintering furnace, and continue to introduce an inert gas into the sintering furnace to remove excess dehydroxylation gas; continue to heat the sintering furnace to a sintering temperature, perform sintering, and after the sintering treatment is completed, finally cool the sintering furnace to obtain a quartz glass blank;
[0074] Step 2: placing the quartz glass blank in the mold cavity of the trough sink furnace, and fixing the quartz glass blank in the mold cavity by cooperating with the pressing plate mold on the pressing plate through the bottom wall; starting the first heating unit and the second heating unit, so that the temperature T1 of the first temperature zone is equal to the temperature of the second temperature zone T2, 1300°C≤T1, T2<1600°C, and maintaining the temperature for at least 60 minutes;
[0075] Step 3: Keep the temperature of the first heating unit unchanged, and heat the second heating unit, so that the temperature T2 of the second temperature zone is 1600°C≤T2≤1800°C. After maintaining the temperature for at least 10 minutes, the cylinder is pressed on the blank along the first direction at a descending speed of 3mm / min to 5mm / min. After the blank fills the concave part of the bottom wall, the cylinder is pressed at a constant extrusion tension of -5N to -2N. At this time, the descending speed of the cylinder is generally 5mm / min to 10mm / min.
[0076] Step 4: After the blank is formed, the cylinder descends to the bottom, and then the second heating unit is heated up so that the temperature of the second temperature zone increases by 20° C. to 50° C. based on step 3, and the temperature is maintained for at least 10 minutes to obtain quartz glass.
[0077] The quartz glass preparation system provided by the present invention is convenient and quick to use, and can prepare large-sized, high-optical uniformity, and low-hydroxyl content quartz glass. The system can avoid the generation of stripes and bubbles after the quartz glass blank is softened, resulting in poor uniformity of the quartz glass. In addition, during the heat treatment, the first differential heat treatment, and the second differential heat treatment of the quartz glass blank, the temperature can be continuously increased or kept constant, which reduces the waste of resources caused by repeated heating and cooling, can reduce production costs, and the preparation process is green and environmentally friendly.
[0078] The present invention will be further described below by means of specific examples and comparative examples.
[0079] In the following Examples 1-5 and Comparative Examples 1-2, the methods for measuring the metal impurity content, hydroxyl content, and optical uniformity in the quartz glass are as follows:
[0080] The metal impurity content is detected using an inductively coupled plasma emission mass spectrometer (ICP-MS) in accordance with the testing standard of "GB / T 3284-2015 Chemical Composition Analysis of Quartz Glass".
[0081] The hydroxyl content is detected by infrared spectrometer according to the detection standard of "GB / T 12442-90 Determination of hydroxyl content in quartz glass".
[0082] Use laser interferometer to detect the optical uniformity △n of quartz glass according to the detection standard of optical uniformity Fizeau plane interferometry method in Appendix A of "JC / T 185-2013 Optical Quartz Glass".
[0083] In the following examples, the tank sink furnace used is as follows Figure 1 As shown, it includes a furnace shell 1, a mold 5 having a mold cavity 8, a pressure unit, a first heating unit 6a and a second heating unit 6b;
[0084] The mold 5 has a mold cavity 8. The mold 5 is located in the heating cavity formed by the furnace shell 1. The mold 5 is mainly composed of a U-shaped graphite mold and a bottom wall 5a for receiving the quartz glass. The bottom wall 5a includes a concave portion 51a located in the center and a flat portion 52a arranged around the concave portion 51a. The concave portion 51a is concave in a direction away from the center of the mold cavity 8.
[0085] The pressure unit is arranged in the mold cavity, and includes a cylinder 2 and a pressing plate 3. The cylinder 2 controls the pressing plate 3 to reciprocate along a first direction in the mold cavity 8. A pressing plate mold 3a is provided on one side of the pressing plate 3 close to the mold cavity, which is used to fix the quartz glass blank 4 in the mold cavity.
[0086] The first heating unit 6a and the second heating unit 6b are located between the furnace shell 1 and the mold 5 and are arranged in sequence along the first direction (from A to B); the first heating unit 6a and the second heating unit 6b correspond to the first temperature zone and the second temperature zone of the mold cavity respectively; a graphite insulation material 7 is arranged between the first heating unit 6a, the second heating unit 6b and the furnace shell 1;
[0087] In the embodiment of the present invention, the bottom surface of the blank 4 is arranged opposite to the recessed portion 51 a , and the quartz glass blank 4 can be fixed in the mold cavity 8 by the bottom wall 5 a cooperating with the pressing plate mold 3 a on the pressing plate 3 .
[0088] Example 1
[0089] (1) a silicon dioxide loose body with a diameter of 320 mm and a height (length) of 1.6 m is prepared by a chemical deposition method, and the silicon dioxide loose body is placed in a sintering furnace, and after dehydroxylation treatment and sintering treatment, a quartz glass blank with a diameter of 200 mm and a height of 1.2 m is obtained;
[0090] (2) placing the quartz glass blank in the mold cavity of the trough sink furnace, and fixing the quartz glass blank in the mold cavity by the bottom wall cooperating with the pressing plate mold on the pressing plate; starting the first heating unit and the second heating unit, so that the temperature of the first temperature zone and the temperature of the second temperature zone are increased to 1400° C. at a rate of 5° C. / min, and maintained at this temperature for 60 minutes;
[0091] (3) Keeping the temperature of the first heating unit unchanged, the second heating unit continues to heat up, so that the temperature of the second temperature zone rises to 1700°C at a rate of 3°C / min. After maintaining this temperature for 10 minutes, the cylinder begins to descend and extrude the blank along the first direction. The descending speed of the cylinder is 3 mm / min to 5 mm / min. After the blank completely fills the concave part of the bottom wall, the cylinder is pressed at a constant extrusion tension of -5N, so that the cylinder descends at a speed of 8 to 10 mm / min.
[0092] (4) After the blank is formed, the cylinder descends to the bottom, and then the second heating unit is heated up so that the temperature of the second temperature zone rises to 1720° C. and the temperature is maintained for 10 minutes to obtain quartz glass.
[0093] The quartz glass obtained in Example 1 has a diameter of Φ360 mm and a thickness of 300 mm. The metal impurity content is less than 1 ppm, the hydroxyl content is less than 1 ppm, and the optical uniformity is 8×10 -6 .
[0094] Example 2
[0095] Compared with Example 1, the step (2) of "maintaining at the temperature for 60 min" is replaced by "maintaining at the temperature for 10 min", and other conditions remain unchanged.
[0096] The quartz glass obtained in Example 2 has a diameter of 360 mm and a thickness of 300 mm. The metal impurity content is less than 1 ppm, the hydroxyl content is 2.1 ppm, and the optical uniformity is 12×10 -6 .
[0097] Example 3
[0098] Compared with Example 1, step (4) is replaced by "after the cylinder is lowered to the bottom blank is formed, quartz glass is obtained", and other conditions remain unchanged.
[0099] The quartz glass obtained in Example 3 has a diameter of Φ360 mm and a thickness of 300 mm. The metal impurity content is less than 1 ppm, the hydroxyl content is less than 1 ppm, and the optical uniformity is 9×10 -6 .
[0100] Example 4
[0101] Compared with Example 1, the step (3) of "raising the temperature of the second temperature zone to 1700°C at a rate of 3°C / min" is replaced by "raising the temperature of the second temperature zone to 1700°C at a rate of 10°C / min", and other conditions remain unchanged.
[0102] The quartz glass obtained in Example 4 has a diameter of 360 mm and a thickness of 300 mm. The metal impurity content is less than 1 ppm, the hydroxyl content is less than 1 ppm, and the optical uniformity is 11×10 -6 .
[0103] Example 5
[0104] (1) a silicon dioxide loose body with a diameter of 400 mm and a height (length) of 1.8 m is prepared by a chemical deposition method, and the silicon dioxide loose body is placed in a sintering furnace, and after dehydroxylation treatment and sintering treatment, a quartz glass blank with a diameter of 240 mm and a height of 1.4 m is obtained;
[0105] (2) placing the quartz glass blank in the mold cavity of the trough sink furnace, and fixing the quartz glass blank in the mold cavity by the bottom wall cooperating with the pressing plate mold on the pressing plate; starting the first heating unit and the second heating unit, so that the temperature of the first temperature zone and the temperature of the second temperature zone are increased to 1400° C. at a rate of 5° C. / min, and maintained at this temperature for 60 minutes;
[0106] (3) Keeping the temperature of the first heating unit unchanged, the second heating unit continues to heat up, so that the temperature of the second temperature zone rises to 1700°C at a rate of 3°C / min. After maintaining this temperature for 10 minutes, the cylinder begins to descend and extrude the blank along the first direction, so that the cylinder descends at a rate of 3 mm / min to 5 mm / min. After the blank completely fills the concave part of the bottom wall, the cylinder is pressed at a constant extrusion tension of -2N, so that the cylinder descends at a rate of 5 to 7 mm / min.
[0107] (4) After the blank is formed, the cylinder descends to the bottom, and then the second heating unit is heated up so that the temperature of the second temperature zone rises to 1720° C. and the temperature is maintained for 10 minutes to obtain quartz glass.
[0108] The quartz glass obtained in Example 5 has a diameter of 400 mm and a thickness of 400 mm. The metal impurity content is less than 1 ppm, the hydroxyl content is less than 1 ppm, and the optical uniformity is 5×10 -6 .
[0109] Comparative Example 1
[0110] Compared with Example 1, the step (3) of "lowering the cylinder at a speed of 8 to 10 mm / min" is replaced by "lowering the cylinder at a speed of 11 to 13 mm / min", and other conditions remain unchanged.
[0111] The quartz glass obtained in Comparative Example 1 has a diameter of 360 mm and a thickness of 300 mm. The metal impurity content is less than 1 ppm, the hydroxyl content is less than 1 ppm, and the optical uniformity is 21×10 -6 .
[0112] Comparative Example 2
[0113] Compared with Example 1, step (3) is replaced by “the first heating unit and the second heating unit continue to heat up, so that the temperature in the tank sink furnace is raised to 1700° C. at a rate of 3° C. / min, and after being kept at this temperature for 10 minutes, the cylinder begins to descend, and the blank is extruded along the first direction, wherein the descending speed of the cylinder is 3 mm / min-5 mm / min, and after the blank completely fills the concave part of the bottom wall, the cylinder is pressed at a constant extrusion tension of -5N, so that the descending speed of the cylinder is 8-10 mm / min; other conditions remain unchanged.
[0114] The quartz glass obtained in Comparative Example 2 has a diameter of 360 mm and a thickness of 300 mm. The metal impurity content is less than 1 ppm, the hydroxyl content is less than 1 ppm, and the optical uniformity is 14×10 -6 .
[0115] Comparative Example 3
[0116] Compared with Example 1, the bottom wall with the recessed portion in the mold is replaced with a common circular bottom wall (without the recessed portion, only the flat portion), and pressure is applied in the bottom wall mold without the recessed portion, while other conditions remain unchanged;
[0117] The quartz glass obtained in Comparative Example 3 has irregular quartz glass fragments on its edge. The output diameter of the quartz glass is Φ360 mm and the thickness is 300 mm. The actual effective diameter is Φ340 mm and the thickness is 290 mm. The metal impurity content is less than 1 ppm and the hydroxyl content is less than 1 ppm. The optical uniformity is 32×10 -6 .
[0118] It can be seen from this that the quartz glass preparation method provided by the present invention can avoid the generation of stripes and bubbles after the quartz glass blank is softened, which leads to the deterioration of the uniformity of the quartz glass, thereby preparing quartz glass with large size, high optical uniformity and low hydroxyl content, and the preparation process is green and environmentally friendly, which can reduce production costs.
[0119] The preferred specific embodiments and experimental verification of the present invention are described in detail above. It should be understood that ordinary technicians in this field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in this technical field through logical analysis or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing large-size quartz glass, characterized in that: The following steps are involved: The silicon dioxide loose body is subjected to dehydroxylation treatment and sintering treatment to obtain a quartz glass blank; Placing the quartz glass blank in a mold cavity for a first differential heat treatment and applying pressure to the quartz glass blank in a first direction to obtain the quartz glass; The mold cavity includes a first temperature zone and a second temperature zone in sequence along the first direction, and the quartz glass blank includes a second portion corresponding to the second temperature zone, and a first portion corresponding to at least a portion of the first temperature zone; In the first differential heat treatment, the temperature of the second temperature region is higher than the temperature of the first temperature region; in the first differential heat treatment, the temperature of the first temperature region is T1, and the temperature of the second temperature region is T2, wherein 1300°C≤T1<1600°C, 1600°C≤T2≤1800°C; During the pressure treatment, the deformation speed of the quartz glass blank is not higher than 10 mm / min; Before the first differential heat treatment, the quartz glass blank is subjected to a soaking treatment; during the soaking treatment, the temperature T1 of the first temperature zone is equal to the temperature T2 of the second temperature zone, 1300°C≤T1, T2<1600°C, and the time is not less than 60 minutes; After the pressure treatment, a second differential heat treatment is also included; the temperature of the second differential heat treatment is 20°C to 50°C higher than the temperature of the second temperature zone in the first differential heat treatment, and the time is not less than 10 minutes; The preparation system of large-size quartz glass for implementing the preparation method comprises at least: A sintering furnace, used for performing dehydroxylation and sintering treatments on the silicon dioxide loose body; A trough sinking furnace comprises a furnace shell, a mold having a mold cavity, a pressure unit, a first heating unit and a second heating unit; The mold cavity is located in a heating cavity formed by the furnace shell, and the first heating unit and the second heating unit are located between the furnace shell and the mold and are arranged in sequence along a first direction; The pressure applying unit is disposed in the mold cavity and reciprocates along the first direction in the mold cavity; The mold cavity has a bottom wall for receiving the quartz glass, and the bottom wall has a recess; The bottom wall includes a concave portion located in the center and a flat portion arranged around the periphery of the concave portion, and the concave portion is concave in a direction away from the center of the mold cavity; The first direction is a height extension direction of the mold cavity, and the second temperature region is closer to the first direction than the first temperature region; The quartz glass prepared by the preparation method has an optical uniformity of 12×10 -6 Below, the metal impurity content is below 1ppm, the hydroxyl content is below 1ppm, the quartz glass diameter is 300mm~400mm, and the thickness is 300~400mm.
2. The preparation method according to claim 1, characterized in that: The heating rate of each heat treatment is 3°C / min to 8°C / min.
3. The preparation method according to claim 1 or 2, characterized in that: During the pressure treatment, the deformation speed of the quartz glass blank is 3 mm / min to 10 mm / min.
4. A large-size quartz glass, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 3.
